Effectiveness of the National Health Insurance (JKN) Policy in Improving Access and Quality of Health Services: A Literature Study - Muh Arfah; A Nur Azizah; Sukmawati Sukmawati; Muhammad Ikram (Jurnal Pengelolaan Kesehatan Berkelanjutan berbasis Kearifan Lokal, 2026)
Indonesia’s National Health Insurance (Jaminan Kesehatan Nasional/ JKN) has become a major policy instrument in expanding healthcare access and supporting the achievement of Universal Health Coverage (UHC). This study aims to analyze the effectiveness of JKN in improving healthcare access and service quality through a literature review approach. Articles published between 2020–2025 were identified from relevant academic sources. A total of 48 articles were initially identified. After duplicate removal and title–abstract screening, 27 articles remained. Following full-text assessment based on the inclusion and exclusion criteria, 5 articles were finally selected for analysis. The findings indicate that JKN has significantly increased healthcare utilization, reduced financial barriers, and accelerated Indonesia’s progress toward UHC. However, disparities in healthcare utilization, regional access, and service quality remain important challenges. Strategic purchasing reforms through Performance-Based Capitation (KBK) have contributed to improving provider performance, while digital transformation through Mobile JKN has enhanced administrative efficiency and user satisfaction. Nevertheless, the effectiveness of these reforms depends on infrastructure readiness, human resource capacity, and monitoring systems. The novelty of this study lies in presenting an integrated perspective linking healthcare access, quality of care, strategic purchasing, and digital transformation in evaluating JKN effectiveness. In conclusion, JKN has demonstrated measurable progress in expanding access, but strengthening financing sustainability, provider capacity, monitoring systems, and equitable digital innovation remains essential to ensure that broader access consistently leads to high-quality health outcomes.